2001
DOI: 10.1161/01.cir.103.14.1832
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Multimarker Testing for Risk Stratification in Chest Pain Units

Abstract: Background-Earlier, rapid evaluation in chest pain units may make patient care more efficient. A multimarker strategy (MMS) testing for several markers of myocardial necrosis with different time-to-positivity profiles also may offer clinical advantages. Methods and Results-We prospectively compared bedside quantitative multimarker testing versus local laboratory results (LL) in 1005 patients in 6 chest pain units. Myoglobin, creatine kinase-MB, and troponin I were measured at 0, 3, 6, 9 to 12, and 16 to 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(33 citation statements)
references
References 23 publications
(19 reference statements)
3
29
1
Order By: Relevance
“…Recent studies indicated that a combination of myoglobin with CK-MB and the troponins may represent a good marker of heart damage but not of skeletal muscle damage. 18 Myoglobin levels within the normal range 19 were found in the present study, with the exception of the non-sportspeople with skeletal muscle injury. Although higher myoglobin levels were shown in injured than in non-injured sportspeople, they were both considerably lower than those observed in injured non-sportspeople.…”
Section: Discussionsupporting
confidence: 59%
“…Recent studies indicated that a combination of myoglobin with CK-MB and the troponins may represent a good marker of heart damage but not of skeletal muscle damage. 18 Myoglobin levels within the normal range 19 were found in the present study, with the exception of the non-sportspeople with skeletal muscle injury. Although higher myoglobin levels were shown in injured than in non-injured sportspeople, they were both considerably lower than those observed in injured non-sportspeople.…”
Section: Discussionsupporting
confidence: 59%
“…Newby et al 9 demonstrated earlier identification of myocardial infarction than laboratory testing and Carragher et al 10 showed expedited decision-making with turnaround times reduced by 55%, but it was not clear whether these led to meaningful changes in patient care. Ng et al 11 compared management with the panel to previous practice and showed a 40% reduction in coronary care unit admissions.…”
Section: Discussionmentioning
confidence: 99%
“…cTnI contributed significantly to the prognostic power of another scoring system for dogs with severe systemic diseases, the physiologic and laboratory evaluation (APPLE) full score in those patients 38. Using immunoassays with high sensitivity for cTnI improved the sensitivity for detection of myocardial injury as compared to older generation cTnI assays 7, 39, 40, 41…”
mentioning
confidence: 99%